Treatment of Skin Tumors with Electrochemotherapy - Ali Asilian; Iman Momeni; Akram Basiri (مجله دانشکده پزشکی اصفهان, 2013)
Electrochemotherapy involves the application of chemotherapy followed by local electrical pulse around the tumor to increase drug delivery into tumor cells. Electroporation is used to increase drug absorbance only for medications whose transport is prevented by plasma membrane. Among all available medicines, bleomycin and cisplatin have been widely studied in pre-clinical and clinical trials. In-vitro observations revealed an increase in cytotoxicity of these drugs after the application of electrical pulses. In-vivo studies have suggested tumor electroporation after local or systemic chemotherapy therapy (electrochemotherapy) as an effective antitumor treatment. This method has also been successfully used in treating primary tumors of cats, dogs, and horses. Pre-clinical research on several types of tumor has clarified the parameters resulting to the effective, local control of tumors. In human clinical trials, electrochemotherapy has been an efficient method for treating advanced diseases with accessible malignant tumors of various types.